Cell Fusion by Various Strains of Newcastle Disease Virus and Their Virulence - Kohn, Alexander (1969)
Some properties of eight strains of Newcastle disease virus (cell-fusing ability, hemolysin, heat stability of hemagglutinin or of hemolysin) do not correlate with virulence of these strains.